Con un pie en dos mundos: Programas de educación bilingüe para niños quechuahablantes en el Cusco - Saroli, Anna (2011)
Moving between two worlds: integrating interculturality in bilingual educationprograms in Cusco, PeruMany indigenous children in Peru are disadvantaged from birth, a situation which is exacerbated by the many deficiencies in the provision of educational services to rural communities. The Ministry of Education and non-governmental organizations are working together with teachers and community members to implement programs whose goal is a truly intercultural bilingual education. This study presents theresults of a research project which compared two rural schools: one follows the state curriculum; the other, more promisingly, works at the community level with the aim of preparing the children to move with confidence between the two worlds which make up the Peru of today. The study shows promising results in the experimental school in the use both of Spanish and of Quechua by the students.